Empowering Future Educators: The Influence of Pedagogical Mentoring on Virtual Collaboration - Hidayati, Ratri Nur; Widodo, Pratomo; Widyantoro, Agus; ., Gunadi; ., Wiyatmi (Journal of Ecohumanism, 2024)
Virtual collaboration is an established pedagogical method in foreign language education, engaging classes in online projects with international partners as a core component of their curricula. This study investigates the crucial role of teachers as pedagogical mentors in virtual collaboration and analyzes the impact of their strategies and techniques on student learning during these online projects. The article begins by proposing a categorization of pedagogical mentoring based on existing literature. It then presents findings from a virtual collaboration project involving initial English teacher education classes in Indonesia, implementing two types of pedagogical mentoring. Through qualitative content analysis, the study identifies the effects of mentoring provided before the collaboration and reveals insights into student learning when their online interactions are incorporated into classroom activities. The article concludes by discussing the limitations and challenges of different pedagogical mentoring approaches in virtual collaboration and offers recommendations for effective pedagogical mentoring in such projects.